Enhancing National Climate Services (ENACTS) in Ethiopia: A participatory demonstration workshop for Key National and International Development Partners - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Ethiopia’s National Meteorological Agency’s (NMA) Enhancing National Climate Services (ENACTS) is a collaborative tool developed by the International Research Institute for Climate and Society (IRI), The Earth Institute at Columbia University, National Meteorological and Hydrological Services (NMHS) which is supported by the World Meteorological Organization (WMO) and international and national partners including the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).